Spatiotemporal transformation of dissolved organic matter along an alpine stream flow path on the Qinghai-Tibet Plateau: importance of source and permafrost degradation - Wang, Yinghui; Spencer, Robert G. M.; Podgorski, David C.; Kellerman, Anne M.; Rashid, Harunur; Zito, Phoebe; Xiao, Wenjie; Wei, Dandan; Yang, Yuanhe; Xu, Yunping (Biogeosciences, 2018)
The Qinghai-Tibet Plateau (QTP) accounts for approximately 70% of global alpine permafrost and is an area sensitive to climate change. The thawing and mobilization of ice-rich and organic-carbon-rich permafrost impact hydrologic conditions and biogeochemical processes on the QTP. Despite numerous studies of Arctic permafrost, there are no reports to date for the molecular-level in-stream processing of permafrost-derived dissolved organic matter (DOM) on the QTP. In this study, we examine temporal and spatial changes of DOM along an alpine stream (3850-3207 m above sea level) by Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS), accelerator mass spectrometry (AMS) and UV-visible spectroscopy. Compared to downstream sites, dissolved organic matter (DOM) at the headstream site exhibited older radiocarbon age, higher mean molecular weight, higher aromaticity and fewer highly unsaturated compounds. At the molecular level, 6409 and 1345 formulas were identified as unique to the active layer (AL) leachate and permafrost layer (PL) leachate, respectively. Comparing permafrost leachates to the downstream site, 59% of AL-specific formulas and 90% of PL-specific formulas were degraded, likely a result of rapid in-stream degradation of permafrost-derived DOM. From peak discharge in the summer to low flow in late autumn, the DOC concentration at the headstream site decreased from 13.9 to 10.2 mg L-1, while the C-14 age increased from 745 to 1560 years before present (BP), reflecting an increase in the relative contribution of deep permafrost carbon due to the effect of changing hydrological conditions over the course of the summer on the DOM source (AL vs. PL). Our study thus demonstrates that hydrological conditions impact the mobilization of permafrost carbon in an alpine fluvial network, the signature of which is quickly lost through in-stream mineralization and transformation.